2005
DOI: 10.1021/ja056116i
|View full text |Cite
|
Sign up to set email alerts
|

Color-Tunable Photoluminescence of Alloyed CdSxSe1-x Nanobelts

Abstract: High-quality CdSxSe1-x nanobelts of variable composition (0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
144
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(155 citation statements)
references
References 15 publications
11
144
0
Order By: Relevance
“…One goal is to have the ability to control the composition of semiconductor alloys and effectively tune the band-gap of a material for a specific function. As a result, various ternary alloys have recently attracted a great deal of attention for their ability to achieve a wide range of band-gaps, [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, nano-materials, such as nano-wires and nano-ribbons, offer greater versatility by providing a wider range of alloy composition and band-gap modulation which is unachievable using traditional epitaxial film materials due to lattice strain at the substrate interface. 13 Ternary chalcogenide semiconductors, particularly cadmium sulpho-selenide (CdS x Se 1Àx ) alloys, have been intensely studied 8,[14][15][16][17][18][19] in part due to the remarkably broad range of stable stoichiometries that can be attained, owing to the small lattice mismatch among the constituent anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One goal is to have the ability to control the composition of semiconductor alloys and effectively tune the band-gap of a material for a specific function. As a result, various ternary alloys have recently attracted a great deal of attention for their ability to achieve a wide range of band-gaps, [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, nano-materials, such as nano-wires and nano-ribbons, offer greater versatility by providing a wider range of alloy composition and band-gap modulation which is unachievable using traditional epitaxial film materials due to lattice strain at the substrate interface. 13 Ternary chalcogenide semiconductors, particularly cadmium sulpho-selenide (CdS x Se 1Àx ) alloys, have been intensely studied 8,[14][15][16][17][18][19] in part due to the remarkably broad range of stable stoichiometries that can be attained, owing to the small lattice mismatch among the constituent anions.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of CdS x Se 1Àx alloy nano-material morphologies have been synthesized, including nano-wires, nano-ribbons, nano-belts, nano-sheets, nano-crystals, and nano-particles with a variety of aspect ratios and stoichiometries. 3,14,16,18,19 The diversity of electronic and spectral properties of CdS x Se 1Àx alloy nanostructures has great potential applications in tunable optoelectronic devices, such as color engineered displays and lighting, 19 multi-spectral detectors, 13 full-spectrum solar cells, 23 and broadly tunable nanolasers. 8,15,24 Therefore, a detailed examination of the electronic structure and corresponding optical emission is essential to determine the full potential of these functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47] On the other hand, hybrid structures consisted of semiconducting organic slabs and strongly luminescent II-VI semiconductor nanostructures offer favorable perspectives through highly saturated, tunable optical properties, in combination with an easy process-ability from solution and low cost of precursors, which is of importance for high-tech applications such as hybrid organic-inorganic light-emitting diodes and solar cells. [48][49][50] In recent years, novel nanostructures of functional II-VI semiconductor chalcogenides, including nanobelts, nanowires, nanosaws, nanocombs and nanowindmills have been synthesized using thermal evaporation method by Wang's group [42,44,[51][52][53][54][55][56][57][58][59][60] and Lee's group. [61][62][63][64][65][66] In contrast to the traditional thermal evaporation routes or chemical vapor deposition (CVD) method, even hard template approaches, solution chemistry based so-called ''soft'' approaches can provide an alternative, convenient, lower temperature, and environmentally friendly pathway for fabrication of advanced inorganic materials with desirable shapes and sizes, [67] which do not rely on drastic conditions (i.e., high temperature, high pressure etc.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Furthermore, the previous studies show that the variation of E g (AB x C 1-x ) can be represented as a quadratic function of composition…”
mentioning
confidence: 99%
“…[18,19] It is suggested that the composition of Zn x Cd 1-x S and CdS x Se 1-x nanobelts is highly dependent on the substrate temperature. [10,11] In our experiment, the silicon substrates were perpendicularly but not horizontally placed on the ceramic boat (see the Experimental Sec. ), and homogeneous composition was obtained on each substrate.…”
mentioning
confidence: 99%